THE ROLE OF PERSONNEL MANAGER TO INCREASE EMPLOYEE MOTIVATION - Titus Indrajaya; Syech Idrus; Suflani Suflani; Nurdin Natan (International Journal of Economy, Education and Entrepreneurship, 2021)
The personnel manager has a vital role in increasing the effectiveness of human resources in the organization. The success of an organization is highly dependent on the activities and creativity of its human resources. The task of a charm manager is always to create conditions so that employees are always passionate about carrying out and carrying out their work. The purpose of this study is to find out how the role of personnel managers in motivating employees' work, and to find out how personnel managers improve employee performance. This research method is a requirement in research, namely ways of thinking and doing that are well prepared to carry out the research process using specific strategies and achieve research objectives. This method uses strict requirements to provide detailed and thorough direction and guidance to high scientific value. This research is in a company engaged in the service sector, namely Hotel X. This research shows that in the implementation of work, every human being is to lead. If equipped with the knowledge and honed with experience, he will be more successful. In implementing the manager's role, it has not been fully implemented following the applicable rules and norms. This performance can be seen from the activities of its employees when they carry out their activities